Comparison of the Rey Auditory Verbal Learning Test (RAVLT) and Digit Test among Typically Achieving and Gifted Students. - KHOSRAVI FARD, Elham; KEELOR, Jennifer L.; BAGHEBAN, Alireza Akbarzadeh; KEITH, Robert W. (Iranian Journal of Child Neurology)
OBJECTIVE: In this study, different kinds of memory were evaluated using Rey Auditory Verbal Learning (RAVLT) test and were compared between two groups of typical and gifted students using Digit Span test. Finally, we determined if working memory interfered with scores in different Rey stages or not. MATERIAL & METHODS: This study was conducted in Tehran City, Iran in 2013. Scores on RAVLT were compared with WISC- R digit span results in a sample of 148 male students aged 12-14 yr old divided into two groups including 75 students in typical school (IQ ranging between 90 and 110) and 73 gifted students (IQs ranging between 110 and 130). RESULTS: Gifted students obtained higher scores than typical students in both Forward Digit Span (FDS) and Backward Digit Span (BDS) and all 9 stages of RAVLT comparing with typical students (P 0.05). The 14 yr old students in both groups had the highest score. There was a high correlation between FDS and the first stage of RAVLT as well as high correlation between BDS and seventh stage of RAVLT. CONCLUSION: Intelligence has effect on better score of memory and gifted subjects had better scores in memory tests, although the intelligence effect in learning was quantitative rather than qualitative. RAVLT is a comprehensive test, which evaluates short-term memory, working memory and long-term memory and besides Digit span test provides precious information about memory and learning of subjects in order to program different student's educational schedules.